Effect of Organizational Role Stress on Job Satisfaction of Commercial Banking Executives in Sri Lanka - Kottawatta, H.; Piyasena, C.C. (My University, 2016)
Role of executives in the commercial banking sector is a key to success and survival of the bank in any context. Success of their working life depends on the maintenance of the high level job satisfaction. Risky and stressfulness are common in their job. Therefore, this study is aimed to find out the effect of organizational role stress on job satisfaction of the executives in the banking sector using 490 executives. Two standard questionnaires were used to gather the primary data and correlation and regression analysis were used to analyses the data. The major finding of the study is that there is moderately negative relationship and impact of role stressors on the job satisfaction of banking executives.
Keywords: Organizational Role Stress; Job Satisfaction; Banking Executives